Parent Education:“Prepare the Child for the Path, Not the Path for the Child” - Eaton, Candace (Maine Policy Review, 2009)
Candace J. Eaton describes why parent education is important and discusses a number of parent-education approaches and programs that currently exist in Maine. She argues that we need to increase access to research-supported programs, parent-education classes, and support groups to all geographic areas of the state and all populations. In this era of reduced funding, Eaton recommends continuous evaluation of program outcomes and the limitation of funding to programs and approaches that show positive improvements.